Computational Modelling of the Structural Integrity following Mass-Loss in Polymeric Charred Cellular Solids. (27th October 2014) - Whitty, J. P. M.; Francis, J.; Howe, J.; Henderson, B.
Abstract : A novel computational technique is presented for embedding mass-loss due to burning into the ANSYS finite element modelling code. The approaches employ a range of computational modelling methods in order to provide more complete theoretical treatment of thermoelasticity absent from the literature for over six decades. Techniques are employed to evaluate structural integrity (namely, elastic moduli, Poisson's ratios, and compressive brittle strength) of honeycomb systems known to approximate three-dimensional cellular chars. That is, reducing the mass of diagonal ribs and both diagonal-plus-vertical ribs simultaneously show rapid decreases in the structural integrity of both conventional and reentrant (auxetic, i.e., possessing a negative Poisson's ratio) honeycombs. On the other hand, reducing only the vertical ribs shows initially modest reductions in such properties, followed by catastrophic failure of the material system. Calculations of thermal stress distributions indicate that in all cases the total stress is reduced in reentrant (auxetic) cellular solids. This indicates that conventional cellular solids are expected to fail before their auxetic counterparts. Furthermore, both analytical and FE modelling predictions of the brittle crush strength of both auxteic and conventional cellular solids show a relationship with structural stiffness.